Body Dissatisfaction Dengan Kepercayaan Diri Pada Mahasiswa Pengguna Instagram : Alvina Damayanti, Netty Merdiaty - Damayanti, Alvina; Merdiaty , Netty (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2024)
This study explains the relationship between Body Dissatisfaction and Confidence, focusing on psychology students at Bhayangkara Jakarta Raya University. This study aims to determine whether there is a relationship between Body Dissatisfaction and Confidence in psychology students. And Using a total of 129 respondents from the psychology faculty of Bhayangkara University. The method used in this study is correlational to see the relationship between the two variables studied, using JASP version 0.16.4. The results show that Body Dissatisfaction is negatively related to Selfconfidence in psychology students at Bhayangkara University. Suggestions for students to be able to regulate the use of Instagram to prevent body dissatisfaction, which reduces student self-confidence, so students will more easily interact and accept themselves.